Modelling the Laser Surface Hardening in a Ferrite and Pearlite Initial Microstructure - Castro-Cerda, F (Taylor and Francis Ltd., 2023)
The present study explores the microstructure and the depth-dependence of hardness after a single pass laser heat-treatment. The initial microstructure was selected as ferrite and pearlite in different fractions, with the aim of studying low, medium, and high carbon steels. A modification of an existing model is proposed, whereby the cementite dissolution is incorporated to better reflect the microstructure evolution during the rapid thermal cycle. It is found that the predictions under the new paradigm show fair agreement with the experimental data. The new model indicates that the correct estimation of the composition of austenite near the transition zone produces a more accurate prediction of the hardness profile, reducing the overestimation obtained in previous works. © 2023 Institute of Materials, Minerals and Mining.